Pengembangan Aplikasi Damora untuk Monitoring Produksi Hortikultura Berbasis Web dan Mobile Menggunakan Metode Waterfall - Muhammad Jaohar Asbara; Rodhiyah Mardhiyyah (Bulletin of Computer Science Research, 2025)
The agricultural sector plays a strategic role in the national economy, contributing 12.53% to Indonesia’s Gross Domestic Product (GDP) in 2023. Temanggung Regency, as one of the country’s horticultural centers, holds significant potential in commodities such as shallots, chilies, and potatoes. However, the production data recording process in this region is still conducted manually using separate spreadsheets across districts, leading to issues such as input errors, data duplication, loss of important information, and delays in analysis and reporting. This study aims to design and develop the Damora information system for recording and monitoring horticultural production, accessible via both web and mobile platforms for agricultural extension workers and government officers. The system was developed using the Waterfall methodology, employing Unified Modeling Language (UML) for system design, the Flutter framework for implementation, and Firebase as a centralized cloud-based database. The development process included requirements analysis, interface and data structure design, system implementation, and testing. Based on black box testing, all main system features functioned as expected, including production data recording, statistical monitoring, history tracking, and visualization of horticultural productivity graphs. In addition, a limited User Acceptance Test (UAT) was conducted involving agricultural extension workers and government staff, indicating that the system is easy to use, enhances reporting efficiency, and improves field data accuracy. The final result is a mobile application for agricultural extension officers and a web-based application for government officers, capable of providing integrated production data, facilitating information access, and supporting continuous monitoring by the Department of Food Security, Agriculture, and Fisheries of Temanggung Regency in the horticultural sector.